Skills and competencies required by a forensic accountant: an exploratory study conducted in sri lanka - Perera, K.H.; Undukoda, J.K. (International Journal of Accounting & Business Finance, 2020)
The 2016 Global Fraud Survey steered by the Association of Certified Fraud Examiners (ACFE) illustrates that the organisations established worldwide lose approximately 5% of their annual revenue due to fraud. With the increase in fraudulent accounting practices all around the world, the need for forensic accountants has increased to look for indicators of suspicious financial activities and fraudulent activities. Regulators continue to increase the responsibility for auditors to detect fraudulent financial statements, however, there is a mismatch between the supply of and demand for auditors with forensic accounting skills. The main objective of the study is to determine whether forensic accountant needs any special skills and competencies in their profession as forensic accountants and to identify the same. The study is conducted based on a sample of professionally qualified accountants in forensic practice and auditing. Data was collected through questionnaire and analysed using Statistical Package of Social Studies (SPSS). The research identified that fraud risk assessment, deductive analysis and diagnostic skills as the highest ranked skills, whereas, the least ranked skill was marketing. It is suggested that the use of forensic accounting procedures or services to detect financial reporting frauds and corruption practices should be increased in organisations by having or recruiting more forensic accountants with required skills and competencies.
Keywords: Forensic accountant; Skills; Frauds; Financial statements